Formas de sinodalidad en los Hechos de los Apóstoles. Lección inaugural del curso 2024-2025 (3-10-2024) - Card Betori, Giuseppe (Isidorianum, 2025)
The article is the written version of the inaugural lecture delivered by Cardinal Betori at the San Isidoro of Sevilla Faculty of Theology for the 2024-2025 academic year. It analyses some features of synodality in various passages from the Acts of the Apostles: the election of Judas' replacement in the college of the Twelve (Acts 1:15-26); the institution of the Seven (Acts 6,1-6); the evangelisation and baptism of Cornelius (Acts 10-11); the call to mission of Barnabas and Saul (Acts 13,1-3); and the assembly in Jerusalem (Acts 15,1-35). In short, the Acts of the Apostles does not offer a definition of synodality, but rather reflects a path of understanding and experience. It is in history that the Church is formed and not in rigid definitions.